2008
DOI: 10.1007/s00442-008-0965-6
|View full text |Cite
|
Sign up to set email alerts
|

Coordination between leaf and stem traits related to leaf carbon gain and hydraulics across 32 drought-tolerant angiosperms

Abstract: We examined 15 traits in leaves and stems related to leaf C economy and water use for 32 co-existing angiosperms at ridge sites with shallow soil in the Bonin Islands. Across species, stem density was positively correlated to leaf mass per area (LMA), leaf lifespan (LLS), and total phenolics and condensed tannins per unit leaf N (N-based), and negatively correlated to leaf osmotic potential and saturated water content in leaves. LMA and LLS were negatively correlated to photosynthetic parameters, such as area-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
83
3
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(107 citation statements)
references
References 46 publications
17
83
3
4
Order By: Relevance
“…P max has been regarded as a representative value of a leaf's potential carbon gain (cf. Mediavilla and Escudero 2003;Wright et al 2004;Kitajima et al 2005;Ishida et al 2008;He et al 2009;Hikosaka and Shigeno 2009;Karagatzides and Ellison 2009;Nagano et al 2009;Reich et al 2009;Santiago and Kim 2009;Sardans et al 2010). However, the mechanistic link between P max and time-integrated carbon gain remains unclear (Kruger and Volin 2006).…”
Section: Discussionmentioning
confidence: 98%
“…P max has been regarded as a representative value of a leaf's potential carbon gain (cf. Mediavilla and Escudero 2003;Wright et al 2004;Kitajima et al 2005;Ishida et al 2008;He et al 2009;Hikosaka and Shigeno 2009;Karagatzides and Ellison 2009;Nagano et al 2009;Reich et al 2009;Santiago and Kim 2009;Sardans et al 2010). However, the mechanistic link between P max and time-integrated carbon gain remains unclear (Kruger and Volin 2006).…”
Section: Discussionmentioning
confidence: 98%
“…Studies which have reported significant variations (e.g. an unpublished study cited in work by Poorter et al (2009) and Ishida et al (2008)) also found that differences due to phylogeny were as large or larger than differences due to phenology.…”
Section: Forest/savanna Differencesmentioning
confidence: 96%
“…The traits of stem woody parts, namely wood density and water content, have a strong relationship with their functional traits, such as drought tolerance, crown architecture, growth rate, survival, and photosynthesis, especially in tropical forests (Bucci et al 2004, Hiromi et al 2012, Inoue et al 2015, Ishida et al 2008, Kenzo et al 2011, Markesteijn et al 2011, Martin et al 2013, Santiago et al 2004. For example, trees with low wood density exhibit a faster growth rate compared with trees of high wood density, whereas trees with high wood density usually have a high survival rate due to their stronger resistance to physical stress, pathogens, and pest attacks (Curran et al 2008, King et al 2005, 2006, Kitajima 1994.…”
Section: Comparison Of Wood Density and Water Content Between Dry Evementioning
confidence: 99%